2020
DOI: 10.3389/fpsyg.2020.01321
|View full text |Cite
|
Sign up to set email alerts
|

The Priest, the Sex Worker, and the CEO: Measuring Motivation by Job Type

Abstract: This study uses latent semantic analysis (LSA) to explore how prevalent measures of motivation are interpreted across very diverse job types. Building on the Semantic Theory of Survey Response (STSR), we calculate "semantic compliance" as the degree to which an individual's responses follow a semantically predictable pattern. This allows us to examine how context, in the form of job type, influences respondent interpretations of items. In total, 399 respondents from 18 widely different job types (from CEOs thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…It seems we are faced with a well-known problem when the structure of attributes found at the inter-individual level is not reproduced at the intra-individual level (Feldman, 1995;Mischel and Shoda, 1998;Molenaar et al, 2003). The effect of individual interpretations of statements on ratings has already been shown (Arnulf et al, 2020); our results showed this effect on the necessary condition for ratings, transitivity, as well.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It seems we are faced with a well-known problem when the structure of attributes found at the inter-individual level is not reproduced at the intra-individual level (Feldman, 1995;Mischel and Shoda, 1998;Molenaar et al, 2003). The effect of individual interpretations of statements on ratings has already been shown (Arnulf et al, 2020); our results showed this effect on the necessary condition for ratings, transitivity, as well.…”
Section: Discussionsupporting
confidence: 80%
“…Besides, individual interpretations of statements were found to deviate from interpretations commonly expected; moreover, these individual interpretations interfered with ratings independently of the strength of the attribute measured. That is, if one understands a statement differently, his/her rating of this statement will reflect not only agreement/disagreement, but also some personal characteristics (Arnulf et al, 2020). Given that ordering attributes requires respondents to unambiguously understand and distinguish paired statements, any deviation of individual interpretation from expected one can intrude ordering and hamper transitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have targeted these issues among specific samples (e.g., medical personnel and certain job groups [ 29 ]) or compared influences based on factors, such as employment hours [ 30 ] and gender [ 31 ]. A previous study on job type tended to focus on details such as motivation [ 32 ]. In other words, most of the existing studies have focused on occupational conditions rather than specific job types, such as those in the white-collar (including professionals), service, and labor (including agricultural, forestry, fishery, craftspeople, and simple laborers) industries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organizational researchers (e.g., Arnulf et al, 2014 , 2018 ) have been able to use latent semantic analysis (LSA) and semantic survey response theory (SSRT) to quantify the semantic similarity between and among scales, items, and survey responses. Latent semantic analysis is a computational model that assesses similarity in language where the similarity of any “given word (or series of words) is given by the context where this word is usually found” (Arnulf et al, 2020 , p. 4). Latent semantic analysis involves establishing a semantic space from a corpus of existing documents (e.g., journal articles, newspaper stories, item sets).…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of semantic similarity resulting from LSA have accounted for a substantive amount of variability in how individuals respond to survey items that purport to measure (a) transformational leadership, motivation, and self-reported work outcomes (60–86%; Arnulf et al, 2014 ), (b) employee engagement and job satisfaction (25–69%; Nimon et al, 2016 ), and (c) perceptions of a trainee program, intrinsic motivation, and work outcomes (31–55%, Arnulf et al, 2019 ). It also appears that personality, demographics, professional training, and interest in the subject matter have an impact on the degree to which an individual's responses follow a semantically predictable pattern (Arnulf et al, 2018 ; Arnulf and Larsen, 2020 , Arnulf et al, 2020 ). While being able to objectively access the degree to which survey responses are impacted by semantics is a great step forward in survey research, such research is often conducted with LSA spaces that are not open and therefore not customizable except by those that have access to the body of text upon which the LSA space is built.…”
Section: Introductionmentioning
confidence: 99%